Impact of wound duration on diabetic foot ulcer healing: evaluation of a new sucrose octasulfate wound dressing. (2nd October 2020) - Lobmann, Ralf; Grünerbel, Arthur; Lawall, Holger; Lüdemann, Claas; Morbach, Stephan; Tigges, Wolfgang; Völkel, Lukas; Rychlik, Reinhard PT
Abstract : Objective: A common and frequent complication of diabetes is diabetic foot ulcers (DFU), which can have high treatment costs and severe adverse events. This study aims to evaluate the effects of wound duration on wound healing and the impact on costs, including treatment with a new sucrose octasulfate dressing compared with a control dressing. Method: Based on the Explorer study (a two-armed randomised double-blind clinical trial), a cost-effectiveness analysis compared four different patient groups distinguished by their wound duration and additionally two DFU treatment options: a sucrose octasulfate dressing and a neutral dressing (as control). Clinical outcomes and total direct costs of wound dressings were evaluated over 20 weeks from the perspective of the Social Health Insurance in Germany. Simulation of long-term outcomes and costs were demonstrated by a five cycle Markov model. Results: The results show total wound healing rates between 71% and 14.8%, and direct treatment costs for DFU in the range of €2482–3278 (sucrose octasulfate dressing) and €2768–3194 (control dressing). Patients with a wound duration of ≤2 months revealed the highest wound healing rates for both the sucrose octasulfate dressing and control dressing (71% and 41%, respectively) and had the lowest direct treatment costs of €2482 and €2768, respectively. The 100-week Markov model amplified the results. Patients with ≤2 months' wound duration achieved wound healing rates of 98% and 88%, respectively and costs of €3450 and €6054, respectively (CE=€3520, €6864). Sensitivity analysis revealed that the dressing changes per week were the most significant uncertainty factor. Conclusion: Based on the findings of this study, early treatment of DFU with a sucrose octasulfate dressing is recommended from a health economic view due to lower treatment costs, greater cost-effectiveness and higher wound healing rates.